A comparison of flavor and tenderness between dry-aged and vacuum-aged beef strip loins - K. Warren; Curtis L. Kastner (Kansas Agricultural Experiment Station Research Reports, 1989)
Starting 3 days postmortem, sections from eight USDA Choice or better, yield grade 4, strip loins were dry-aged (aged unpackaged) or vacuum-aged (aged in vacuum bags) for an additional 11 days. The dry-aged loins lost more (P<.05) weight during aging than vacuum-aged loins, and cooked faster, with less (P<.05) cooking loss than the unaged loins. Vacuum-and dry-aged samples were similar (P>.05) in tenderness, and both were more tender (P<.05) than unaged counterparts. A trained taste panel found no differences in subcutaneous fat flavor. However, lean from the vacuum-aged samples had a more intense sour flavor note and more intense bloody/serumy flavor and metallic notes than either of the other treatments. The lean of dry-aged samples was beefier and had more brown/roasted flavor than vacuum-aged or unaged counterparts.
Keywords: Cattlemen& #x27; s Day; 1989; Kansas Agricultural Experiment Station contribution; no. 89-567-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 567; Beef; Flavor; Tenderness; Dry-aged; Vacuum-aged; Strip loins